2020
DOI: 10.1094/pdis-10-19-2224-re
|View full text |Cite
|
Sign up to set email alerts
|

Fungicide Application Timing Essential for the Management of Leaf Spot and Fruit Rot on Pomegranate (Punica granatumL.) in Florida

Abstract: Pomegranate (Punica granatum L.) has emerged as an alternative fruit crop for growers dealing with devastating threats to citrus and avocado in the southeastern United States. However, foliar and fruit diseases are major constraints to commercial pomegranate production. Replicated field trials were performed in 2015 at three separate sites in Florida (Dover, Plant City, and Parrish) to evaluate Merivon (pyraclostrobin and fluxapyroxad), Luna Experience (fluopyram + tebuconazole), and a rotational program consi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 33 publications
0
6
0
Order By: Relevance
“…The results observed in this study are in line with those pointed out by Oliveira et al, (2021), who found that pyraclostrobin + fluxapyroxad reduced up to 55% the AUDPC of anthracnose (Colletotrichum truncatum) in soybean plants. Xavier and Vallad (2020) observed lower disease severity and greater control after evaluating this active ingredient for controlling the leaf spot on pomegranates. Ribeiro et al, (2019) studied pyraclostrobin + fluxapyroxad, associated with the protective fungicide Mancozeb, and observed less progress of the target spot (Corynespora cassiicola) in soybean.…”
Section: Resultsmentioning
confidence: 89%
“…The results observed in this study are in line with those pointed out by Oliveira et al, (2021), who found that pyraclostrobin + fluxapyroxad reduced up to 55% the AUDPC of anthracnose (Colletotrichum truncatum) in soybean plants. Xavier and Vallad (2020) observed lower disease severity and greater control after evaluating this active ingredient for controlling the leaf spot on pomegranates. Ribeiro et al, (2019) studied pyraclostrobin + fluxapyroxad, associated with the protective fungicide Mancozeb, and observed less progress of the target spot (Corynespora cassiicola) in soybean.…”
Section: Resultsmentioning
confidence: 89%
“…In addition, arranging pomegranates in microperforated plastic bags can reduce fruit dehydration allowing transpiration and minimizing condensation, indeed it is possible to further extend the storage life of fruit. These bags create a modified atmosphere [76].…”
Section: Disease Controlmentioning
confidence: 99%
“…(Thomidis and Filotheou, 2016;Munhuweyi et al, 2016bMunhuweyi et al, , 2017Brighenti et al, 2021) or biocontrol agents (e.g. Bacillus amyloliquefaciens, B. subtilis) (Ma et al, 2013(Ma et al, , 2015Tekiner et al, 2020) showed to be effective in the orchard controlling leaf spot and fruit rot on pomegranate (Mahla and Ashok, 1989;Gaikwad, 2000;Xavier et al, 2020;Yang et al, 2021), but some of them have been revoked in the EU.…”
Section: Entry/establishment/ Impactmentioning
confidence: 99%